"Design-Led Space" Series Show Flat Design - Taking Dongjin Century City in Xiangyang as An Example. Issue 1 (September 2020) - Huang, Wenjuan; Liu, Yang
Abstract: With the acceleration of our country's urbanization process and the rapid development of the social economy, the urban living thought, the sense of high quality in everyday life and the upgrade of the entire social environment have contributed to the rapid rise of the real estate market, and different types of residential communities and commercial housing continue to emerge. As show flat design is the most important marketing method and marketing hot spot in the real estate market, a show flat design case with great design sense and artistry can often attract consumers' attention at the first time, effectively transfer spatial information of the real estate, show the functional advantages of the house, and give future residents a sense of identity and confidence in the project. This article took three types of show flats in different design styles in the Dongjin Century City project in Xiangyang as an example to deeply analyze the spatial function analysis, color, soft decoration, light source and other factors that should be paid attention to during the design of the show flat, summarized the design-led and people-oriented principles, and created a show flat design in line with practical and functional factors of residence, to achieve the ultimate artistry, exhibition and marketing of show flats.